Cerebrospinal fluid biomarkers provide evidence for kidney-brain axis involvement in cerebral malaria pathogenesis - Conroy, Andrea L.; Datta, Dibyadyuti; Opoka, Robert O.; Batte, Anthony; Bangirana, Paul; Gopinadhan, Adnan; Mellencamp, Kagan A.; Akcan-Arikan, Ayse; Idro, Richard; John, Chandy C. (Frontiers in Human Neuroscience, 2023)
Introduction. Cerebral malaria is one of the most severe manifestations of malaria and is a leading cause of acquired neurodisability in African children. Recent studies suggest acute kidney injury (AKI) is a risk factor for brain injury in cerebral malaria. The present study evaluates potential mechanisms of brain injury in cerebral malaria by evaluating changes in cerebrospinal fluid measures of brain injury with respect to severe malaria complications. Specifically, we attempt to delineate mechanisms of injury focusing on blood-brain-barrier integrity and acute metabolic changes that may underlie kidney-brain crosstalk in severe malaria. Methods. We evaluated 30 cerebrospinal fluid markers of inflammation, oxidative stress, and brain injury in 168 Ugandan children aged 18 months to 12 years of age hospitalized with cerebral malaria. Eligible children were infected with Plasmodium falciparum and had unexplained coma. Acute kidney injury (AKI) on admission was defined using the Kidney Disease: Improving Global Outcomes criteria. We further evaluated blood-brain-barrier integrity and malaria retinopathy, and electrolyte and metabolic complications in serum. Results. The mean age of children was 3.8 years (SD, 1.9) and 40.5% were female. The prevalence of AKI was 46.3% and multi-organ dysfunction was common. AKI and elevated BUN, but not other measures of disease severity (severe coma, seizures, jaundice, acidosis), were associated with increases in several markers in the CSF including markers of impaired blood-brain-barrier function, neuronal injury (neuron-specific enolase, tau), excitatory neurotransmission (kynurenine), as well as altered nitric oxide bioavailability and oxidative stress. Further evaluation of potential mechanisms suggested that AKI may mediate or be associated with CSF changes through blood-brain-barrier disruption, uremia, altered osmolality and through alterations in the amino acids transported into the brain. Conclusions. In children with cerebral malaria, there is evidence of kidney-brain injury with multiple potential pathways identified. These changes were specific to the kidney and not seen in the context of other clinical complications.